223 MECHANICAL STRETCH STIMULATES α-EPITHELIAL NA+ CHANNEL EXPRESSION IN MURINE LUNG EPITHELIAL CELLS: ROLE OF MAPKS. (1st January 2005) - Isaac, J.; DiGeronimo, R. J.; Dixon, P.; Henson, B. M.; Mustafa, S. B.
Abstract : Mechanical stretch of the alveolar epithelium initiates the transduction of intracellular signals in alveolar epithelial cells that elicit numerous cellular responses. Alveolar epithelial Na+ channels (ENaC), in particular the α-subunit, are essential for the maintenance of fluid-free lungs. We studied the effect of mechanical stretch on the expression of α-ENaC in murine lung epithelial (MLE-12) cells. MLE-12 cells were cultured on flexible collagen-coated membranes and exposed to either cyclic (20% strain, 30 cycles/min) or static (10% strain) stretch for up to 24 h. A significant rise in α-ENaC mRNA expression over resting cells occurred 3 h after either cyclic or static stretch. This increase in α-ENaC mRNA expression was attenuated in the presence of actinomycin D. Cyclic stretch induced a 3.4-fold increase and static stretch a 3.2-fold increase in α-ENaC protein after 24 h compared to resting cells. This response was reduced when stretched in the presence of cycloheximide. Cell counts and 3[H] leucine incorporation increased over 24 h in all study groups and were comparable between resting and either static or cyclic stretched cells. In resting cells, low levels of α-ENaC protein were intracellularly localized as detected by immunofluorescence. After cyclic stretch for 24 h, α-ENaC protein was elevated and appeared interspersed at the cell membrane, whereas after static stretch for 24 h, increased α-ENaC protein appeared in a better-defined pattern at the cell membrane. Exposure of MLE-12 cells to either static or cyclic stretch for 2 h caused activation of the mitogen-activated protein kinase (MAPK) pathways; extracellular signal-regulated protein kinase (ERK1, 2), p38 MAPK and the stress-activated protein kinase/c-Jun NH2-terminal kinase (SAPK/JNK). Inhibition of ERK1, 2 by PD98059 did not inhibit the cyclic or static stretch-induced increases in α-ENaC protein, whereas inhibition of p38 MAPK by SB203580 and inhibition of SAPK/JNK by JNK inhibitor II significantly attenuated the increase in either cyclic or static stretch-induced α-ENaC protein after 24 h. From our study, we conclude that either cyclic or static stretch of MLE-12 cells for 24 h induces de novo synthesis of α-ENaC protein. This increase in α-ENaC protein is mediated at least in part by the MAPK pathways, specifically the p38 and JNK pathways.